Conversor CA-CC boost interleaved híbrido a capacitor chaveado com elevado fator de potência - Guimaraes, Julio Cesar (2022)
In this work a single-phase boost PFC multilevel interleaved high voltage gain rectifier based on hybrid switched-capacitor concept is presented. The proposed rectifier merges interphase transformers and switched-capacitors cells in order to obtain current sharing and high voltage gain. These features allow the both reduction of voltage and current stresses on the semiconductors. Additionally, the interleaving method allow to obtain multilevel voltages at ac terminals, thus reducing the weigh and bulk of input inductor. The PFC operation is guaranteed through the both input current control and output voltage control. Both steady-state and dynamic analysis are investigated. Experimental results for a 1.25 kW, 127 V to 800 V laboratory prototype are presented and discussed.